2002
DOI: 10.1348/135910702169358
|View full text |Cite
|
Sign up to set email alerts
|

The affective beneficence of vigorous exercise revisited

Abstract: OBJECTIVES: High exercise intensity may be associated with reduced adherence to exercise programmes, possibly because it is perceived as aversive. However, several authors have suggested that an intensity as high as 60% or 70% of maximal aerobic capacity (VO(2max)) is necessary for exercise to elicit positive affective changes. To elucidate this discrepancy, the affective responses to increasing levels of exercise intensity were examined. DESIGN: In total, 30 volunteers rated their affect every minute as they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
171
3
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(195 citation statements)
references
References 71 publications
20
171
3
1
Order By: Relevance
“…Previous studies have shown that (a) when participants are allowed to select their preferred intensity, they intuitively tend to gravitate toward a level that approximates the point of transition from an intensity that can be maintained through aerobic metabolism to an intensity that requires anaerobic supplementation, operationalized as a threshold in blood lactate accumulation or gas exchange 47,48 and (b) a systematic decrease in self-ratings of pleasure begins once the intensity exceeds the level of the aerobic-anaerobic transition. [49][50][51][52] In analyses not detailed here, we found that normal-weight and overweight participants did not differ in terms of the level of oxygen uptake they utilized in relation to their gas exchange threshold (used as an indirect, noninvasive marker of the aerobic-anaerobic transition) in either the self-selected or the imposed-intensity condition. In the self-selected intensity condition, the intensity remained below the gas exchange threshold for the entire duration of the bout (78, 85, 93, and 97% of the oxygen uptake at the gas exchange threshold at min 5, 10, 15, and 20, respectively).…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies have shown that (a) when participants are allowed to select their preferred intensity, they intuitively tend to gravitate toward a level that approximates the point of transition from an intensity that can be maintained through aerobic metabolism to an intensity that requires anaerobic supplementation, operationalized as a threshold in blood lactate accumulation or gas exchange 47,48 and (b) a systematic decrease in self-ratings of pleasure begins once the intensity exceeds the level of the aerobic-anaerobic transition. [49][50][51][52] In analyses not detailed here, we found that normal-weight and overweight participants did not differ in terms of the level of oxygen uptake they utilized in relation to their gas exchange threshold (used as an indirect, noninvasive marker of the aerobic-anaerobic transition) in either the self-selected or the imposed-intensity condition. In the self-selected intensity condition, the intensity remained below the gas exchange threshold for the entire duration of the bout (78, 85, 93, and 97% of the oxygen uptake at the gas exchange threshold at min 5, 10, 15, and 20, respectively).…”
Section: Discussionmentioning
confidence: 67%
“…However, assessments of affective responses during the activity bout have shown that, as intensity increases, there are consistent decreases in self-rated pleasure and, eventually, increases in displeasure during the activity (Acevedo, Kraemer, Haltom, & Tryniecki, 2003;Acevedo, Rinehardt, & Kraemer, 1994;Bixby, Spalding, & Hatfield, 2001;Ekkekakis, Hall, & Petruzzello, 2004;Hall, Ekkekakis, & Petruzzello, 2002;Hardy & Rejeski, 1989;Parfitt & Eston, 1995;Parfitt, Eston, & Connolly, 1996;Parfitt, Markland, & Holmes, 1994). Upon cessation of the intense activity, the typically negative changes are followed by rapid positive changes, leading to a post-activity state that is more pleasant than the pre-activity one (Bixby et al, 2001;Hall et al, 2002). Thus, the consequence of this problem is that a dose -response pattern that is apparent during the activity may quickly dissipate as soon as the activity is terminated.…”
Section: Two Methodological Pitfallsmentioning
confidence: 99%
“…Strong evidence exists for physical activity as a factor in reducing the risk of diabetes [1], osteoporosis [2], heart disease [3] and some forms of cancer [4]. Evidence for the role of physical activity in psychological well-being also has accumulated, with research indicating that physical activity may be effective in treating and/or reducing the risk of depression and anxiety [5].…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%